Role of Oxidative Stress in Retinal Photoreceptor Cell Death in N-Methyl-N-nitrosourea-Treated Mice - Kazuhiro Tsuruma; Mika Yamauchi; Yuta Inokuchi; Sou Sugitani; Masamitsu Shimazawa; Hideaki Hara (Elsevier, 2012)
This study aimed to investigate whether oxidative stress contributes to retinal cell death in a mouse model of photoreceptor degeneration induced by N-methyl-N-nitrosourea (MNU). We measured in vitro MNU-induced radical production in retinal cell cultures of murine 661W photoreceptor-derived cells; RGC-5, a mouse ganglion cell line; and primary retinal cells. The addition of MNU induced oxidative radical generation in 661W and primary retinal cells, but not in RGC-5 cells. Edaravone, a free radical scavenger, at 1 μM reduced MNU-induced radical production in 661W and primary retinal cells. To induce in vivo retinal photoreceptor degeneration in mice, we administered 60 mg/kg MNU by intraperitoneal injection. We intravenously administered 1 mg/kg edaravone immediately and at 6 h after the MNU injection. Retinal photoreceptor degeneration was evaluated by measuring the thickness of the outer nuclear layer (ONL) by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining and by oxidative stress markers. MNU caused photoreceptor cell loss at 7 days after administration. Edaravone inhibited ONL thinning and reduced TUNEL-positive cells and the oxidative stress markers. These findings indicate that MNU leads to selective photoreceptor degradation via oxidative stress in vitro and in vivo and may help to understand the pathogenic mechanism of retinitis pigmentosa. Keywords:: edaravone, N-methyl-N-nitrosourea, oxidative stress, photoreceptor, retinitis pigmentosa